Transesterification of Waste Frying Oil Using Alkaline Activated Waste Marble Catalyst: Effects of Process Parameters, Modeling, and Optimization - Allen, M. A.; Nwosu-Obieogu, K.; Erokare, T. E.; Okoye, J.; Francis, M. U.; Nwogu, C. N.; Itiri, H. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2025)
Through calcination at 600oC for four hours, a novel alkaline activated waste marble heterogeneous catalyst was produced and successfully used for biodiesel synthesis from waste frying oil. To determine the catalyst's appropriateness for the process, Scanning Electron Micrograph (SEM), X-ray Diffraction (XRD), Brunauer-Emmett-Teller (BET) and Fourier Transform Infrared Spectroscopy (FT-IR) were used. Similarly, to determine the waste frying oil's suitability for the transesterification process, FT-IR and GC-MS (Gas Chromatography Mass Spectrometer) were applied in its characterization. The variables (time, temperature, catalyst dosage, methanol/mol ratio and agitation speed) were considered during the transesterification process, and an increase in the process parameters significantly affected the yield. In addition, Response surface methodology (RSM) was applied to optimize the best conditions; the second-order polynomial model is displayed in the Analysis of Variance (ANOVA) with an R2 value of 0.9564, Adj R2 (0.9216), and Pred R2 (0.8257), indicating the acceptability of the model. The optimal yield of biodiesel (86.25%) was obtained at a catalyst concentration of 2.52wt. %, methanol/molar ratio of 6.14mol/mol, time of 1.10 hours, temperature of 59.8oC and agitation speed of 325.2rpm. Interestingly, the WFO biodiesel produced complied with ASTM D6751 requirements.